2018
DOI: 10.1159/000487955
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Improves Sepsis-Induced Mortality and Acute Kidney Injury

Abstract: Objectives: Icariin (ICA) is a bioactive flavonoid with renal protective actions. This study investigated the effects of ICA on renal injury, inflammation, oxidative damage, apoptosis, and survival in a mouse model of cecal ligation and perforation (CLP)-induced sepsis. Methods: Sepsis was induced by CLP. Mice were treated with ICA (30 or 60 mg/kg) for 3 days before CLP. Renal functions, inflammatory responses, oxidative damage, histological changes, apoptosis, and vascular permeability were examined. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The main characteristics and results of the human studies evaluating the potential reno-protective effects of PDE5Is are summarized in Table 1 [17,24,38,39]. The main characteristics and results of the animal studies on currently proposed AKI models evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table 2 [23,30,, Table 3 [29,35,45,49,[62][63][64][65][66][67][68][69][70][71][72][73][74], Table 4 [18,75,76], Table 5 [45,77,78], and Table 6 [21,40,79,80], respectively. The main characteristics and results of the animal studies in the AKI-CKD transition spectrum (focusing on renal function and/or structure alterations for up to three months, not fulfilling the KDIGO definition for CKD [6]) evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table A1 [109,110], respectively (Appendix B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics and results of the human studies evaluating the potential reno-protective effects of PDE5Is are summarized in Table 1 [17,24,38,39]. The main characteristics and results of the animal studies on currently proposed AKI models evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table 2 [23,30,, Table 3 [29,35,45,49,[62][63][64][65][66][67][68][69][70][71][72][73][74], Table 4 [18,75,76], Table 5 [45,77,78], and Table 6 [21,40,79,80], respectively. The main characteristics and results of the animal studies in the AKI-CKD transition spectrum (focusing on renal function and/or structure alterations for up to three months, not fulfilling the KDIGO definition for CKD [6]) evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table A1 [109,110], respectively (Appendix B).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the insult type, there are various mechanisms leading to renal damage such as renal vasoconstriction [17], vascular endothelial damage, cytokine expression [18], increase of IL-18, mediating acute tubular necrosis, caspase activity stimulation, p53 up-regulation [19], accumulation of toxic metabolites [20], mast cells/neutrophils activation, reactive oxygen species (ROS) generation causing lipid peroxidation that leads to cellular membrane destruction, excessive intracellular DNA breakdown, energy depletion, intracellular Ca2+ elevation, higher inducible nitric oxide (NO) synthase (iNOS) expression, NO deficiency, intra-parenchymal hemorrhage [21], fibrosis, direct cellular toxicity, tubular obstruction, vascular congestion, activation of angiotensin II axis [22], mitochondrial dysfunction [23], cell cycle arrest in G2 phase, ATPase activity inhibition, and cellular transport modification. ROS activate pro-apoptotic proteins eventually promoting Bax translocation (regulated by PI3K/Akt pathway) to the outer mitochondrial membrane, causing the release of cytochrome c in the cytosol [24].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Xie et al reported a protection of icariin against inflammatory response, apoptosis and vascular permeability in a sepsis-induced AKI mouse model. 24 In another unilateral ureteral obstruction mouse model, icariin also mitigated several proinflammatory factors, such as NF-κB, cyclooxygenase-2 and interleukin 1β. 10 Thus, the universal anti-inflammation and anti-apoptosis effect of icariin may contribute to its remarkable protection in CIAKI model, as the improved renal function and alleviated histological injury were demonstrated in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, polyphenolic antioxidant flavonoid consumption improves endotoxemia and septic condition. Several types of flavonoids improve MODS and increase survival against sepsis [ 36 , 37 , 38 ]. The evidence suggests that the nutrient composition of food affects sepsis progression and its outcomes, but the molecular underlying mechanism has not been completely described.…”
Section: Introductionmentioning
confidence: 99%